Greenwashing and the challenge of sustainable development in the construction industry - Pham Ngoc Thinh (Tạp chí Khoa học và Công nghệ)
Greenwashing, defined as the dissemination of inaccurate or misleading information regarding the environmental performance of products, services, or brands, has become increasingly prevalent in the construction industry. This study examines the extent and consequences of greenwashing in the sector, focusing on how exaggerated sustainability claims influence stakeholder trust and decision-making. Employing a mixed-methods approach - incorporating content analysis of corporate sustainability reports and surveys of industry experts - the research identifies common greenwashing strategies and evaluates their effects. Findings reveal that overstated environmental claims are pervasive, contributing to a significant decline in stakeholder trust. The discussion addresses the ethical implications of greenwashing, the challenges associated with its detection, and offers solutions to enhance transparency and accountability. This study advances the understanding of greenwashing within the construction industry and provides actionable recommendations to mitigate its negative impact on sustainability initiatives.